Cochrane Database of Systematic Reviews 2010
DOI: 10.1002/14651858.cd007482.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic prophylaxis versus no prophylaxis for preventing infection after cesarean section

Abstract: Endometritis was reduced by two thirds to three quarters and a decrease in wound infection was also identified. However, there was incomplete information collected about potential adverse effects, including the effect of antibiotics on the baby, making the assessment of overall benefits and harms complicated. Prophylactic antibiotics given to all women undergoing elective or non-elective cesarean section is clearly beneficial for women but there is uncertainty about the consequences for the baby.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
108
7
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 261 publications
(123 citation statements)
references
References 111 publications
(204 reference statements)
3
108
7
5
Order By: Relevance
“…The potential of antibiotic prophylaxis during cesarean delivery to reduce the number of postpartum maternal infections has been studied in many clinical trials and meta-analyses [5,6,7,8]. It is worth mentioning that a Cochrane review updated by Smaill and Gyte [8] in 2010 concluded that prophylactic antibiotics given to all women undergoing elective or nonelective cesarean section was clearly beneficial.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential of antibiotic prophylaxis during cesarean delivery to reduce the number of postpartum maternal infections has been studied in many clinical trials and meta-analyses [5,6,7,8]. It is worth mentioning that a Cochrane review updated by Smaill and Gyte [8] in 2010 concluded that prophylactic antibiotics given to all women undergoing elective or nonelective cesarean section was clearly beneficial.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth mentioning that a Cochrane review updated by Smaill and Gyte [8] in 2010 concluded that prophylactic antibiotics given to all women undergoing elective or nonelective cesarean section was clearly beneficial. Driven by concerns about the sequelae of fetal antibiotic exposure with preincision administration, for nearly 30 years the standard to prevent postcesarean infection has been the administration of narrow-spectrum antibiotic prophylaxis after delivery of the baby and clamping of the umbilical cord [8,9]. …”
Section: Introductionmentioning
confidence: 99%
“…They are associated with decrease in incidence of endometritis of 62%, in wound infection of 61%, in fever of 55%, and in serious maternal infectious complications by 69% (10,11). Urinary tract infections (UTI) are also markedly decreased.…”
Section: Prophylactic Antibioticsmentioning
confidence: 99%
“…Later-generation (e.g., second or third), or more expensive broad-spectrum agents, do not improve efficacy further (11). A multiple-dose regimen for prophylaxis appears to offer no added benefit over a single-dose regimen (10,11). Systemic (after cord clamping) …”
Section: Which Antibiotics To Use and Howmentioning
confidence: 99%
See 1 more Smart Citation